2017
DOI: 10.1007/s00520-017-3724-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep disturbance with physical function and cognition in older adults with cancer

Abstract: Purpose Although sleep disturbances are common in older adults, studies evaluating the prevalence of sleep disturbance and influence on functional outcomes in older adults with cancer are few. In this study, we examined the prevalence of sleep disturbance and its association with physical function and cognition in older adults with cancer. Methods Patients referred to the Specialized Oncology Care & Research in the Elderly clinics at the Universities of Rochester and Chicago from May 2011 to October 2015 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 67 publications
(62 reference statements)
1
30
1
2
Order By: Relevance
“…Since there is no established BOMC cut point for CRCI, it would be useful to investigate an appropriate threshold for use in this population. In this regard, a recent study evaluating the relationship between cognition and sleep disturbance in older patients with cancer defined cognitive impairment a priori at the far lower threshold of BOMC >4 . Using this lower threshold, Loh et al found that 47% suffered from cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no established BOMC cut point for CRCI, it would be useful to investigate an appropriate threshold for use in this population. In this regard, a recent study evaluating the relationship between cognition and sleep disturbance in older patients with cancer defined cognitive impairment a priori at the far lower threshold of BOMC >4 . Using this lower threshold, Loh et al found that 47% suffered from cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally developed for detection of dementia, has good reliability and validity, but has not been well studied for assessment of mild cognitive impairment or change . The BOMC has been included in cancer‐specific geriatric assessments, investigated as a potential covariate for other outcomes of interest in cancer (eg, sleep disturbance, quality of life, disease‐specific outcomes), and is highly correlated with and predictive of the trajectory of self‐reported cognitive function in a cohort of older breast cancer survivors . Despite these compelling features, the BOMC has not previously been described as a primary outcome measure for the evaluation of CRCI.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of interest were physical function measures captured in the GA including instrumental activities of daily living (IADL) status measured by difficulty using a telephone, managing money, managing medications, grocery shopping, preparing meals, doing housework, and using transportation; Medical Outcomes Survey (MOS) physical activity (PA) survey eliciting significant limitations in performing 10 activities such as lifting or carrying groceries, climbing several flights of stairs, and walking more than one mile; SPPB as an objective measure of physical performance including lower extremity physical function by performing a 4‐meter walk, repeated chair stands, and a balance test; and falls in the previous 6 months. Four separate measures of functional impairment were created based on the instruments described above: 1, any assistance required for IADL task; 2, any significant limitation on MOS PA survey; 3, history of at least one fall in the previous 6 months; and 4, SPPB score of 9 or less …”
Section: Methodsmentioning
confidence: 99%
“…In older adults, several factors contribute to medication non-adherence. For example, older adults are less likely than younger adults to ask questions about cancer therapies, 41 leading providers to assume they have a better grasp of how and why to take their medications than they may actually have; cognitive impairment (present in about 25–47% of older patients with cancer)[55, 56] and hearing loss (present in 25% of older patients with cancer)[2] can magnify this issue. Older patients often have difficulties with transportation, leading to missed appointments or unfilled prescriptions [57, 58].…”
Section: Medication Adherencementioning
confidence: 99%